Characterization of nano‐hydroxyapatite incorporated carboxymethyl chitosan composite on human dental pulp stem cells. (12th January 2023) - Gurucharan, Ishwarya; Saravana Karthikeyan, Balasubramanian; Mahalaxmi, Sekar; Baskar, Kaviya; Rajkumar, Gurusamy; Dhivya, Vijayakumar; Kishen, Anil; Sankaranarayanan, Seshadri; Gurucharan, Natanasikamani
Abstract: Aim: To compare the odontogenic differentiation potential of a composite scaffold (CSHA) comprising of nano‐hydroxyapatite (nHAp) and carboxymethyl chitosan (CMC) with Biodentine on human dental pulp stem cells (hDPSCs). Methodology: A CSHA scaffold was prepared through an ultrasonication route by adding nHAp and CMC (1:5 w/w) in water medium followed by freeze‐drying. Physicochemical characterization was achieved using scanning electron microscopy with energy‐dispersive X‐ray spectroscopy, X‐ray diffraction and Fourier transform infrared spectroscopy. In‐vitro bioactivity and pH assessments were done by soaking in simulated body fluid (SBF) for 28 days. The angiogenic and odontogenic differentiation abilities were assessed by expression of vascular endothelial growth factor (VEGF) and Dentine sialophosphoprotein (DSPP) markers on cultured hDPSCs by flow cytometry and RT‐qPCR at 7, 14 and 21 days. Cell viability/proliferation and biomineralization abilities of CSHA were compared with Biodentine by MTT assay, alkaline phosphatase (ALP) activity, Alizarin Red Staining (ARS) and osteopontin (OPN) expression on hDPSCs following 7 and 14 days. Data were statistically analysed with Kruskal Wallis and Friedman tests as well as one way anova followed by appropriate post hoc tests ( p < .05). Results: Characterization experiments revealed a porous microstructure of CSHA with pore diameter ranging between 60 and 200 μm and 1.67 Ca/P molar ratio along with the characteristic functional groups of both HAp and CMC. CSHA displayed bioactivity in SBF by forming apatite‐like crystals and maintained a consistent pH value of 7.70 during 28 days' in vitro studies. CSHA significantly upregulated VEGF and DSPP levels on hDPSCs on day 21 compared with day 7 ( p < .05). Further, CSHA supported cell viability/proliferation over 14 days like Biodentine with no statistical differences ( p > .05). However, CSHA exhibited increased ALP and ARS activity with an intense OPN staining compared with Biodentine after 14 days ( p < .05). Conclusion: The results highlighted the odontogenic differentiation and biomineralization abilities of CSHA on hDPSCs with significant VEGF and DSPP gene upregulations. Further, CSHA exhibited enhanced mineralization activity than Biodentine, as evidenced by increased ALP, ARS and OPN activity on day 14. The nHAp‐CMC scaffold has the potential to act as an effective pulp capping agent; however, this needs to be further validated through in‐vivo animal studies.